Unlocking the impact: a systematic review and meta-analysis of biomechanical insights into rugby head impacts using wearable sensor technology - De Sousa-De Sousa, L.; Espinosa, H. G.; Maté-Muñoz, J. L.; Murias-Lozano, R.; Iglesias Muñiz, M.; San Sebastián Obregón, F. J.; Solís-Mencía, C.; García-Fernández, P. (Sports Medicine, 2025)
Background: In the realm of sports medicine, understanding the biomechanics of head impacts, particularly in contact sports such as rugby, is of utmost interest for injury prevention and player safety. Objective: This systematic review and meta-analysis aims to consolidate existing knowledge on head impacts in rugby using wearable sensor technology, focusing on peak linear acceleration, peak rotational acceleration, and impact location. Methods: A systematic search of electronic databases [PubMed, Web of Science (WOS), Scopus, Embase, SPORTDiscus, PsycINFO, and CINAHL] was conducted in March 2024, including studies that assessed head impacts with wearable technology in rugby athletes. The search did not impose any restrictions on publication dates and included studies published in English and Spanish. A random-effects meta-analysis model was employed to combine comparable data from the included studies. Results: The literature search yielded 13 prospective cohort studies, collectively analyzing 895 participants and 44,036 head impacts. Most studies were conducted in Australasia and North America, with varying levels of play represented, from junior to semi/professional and from both rugby codes, rugby union (RU) and rugby league (RL). Wearable sensors, including instrumented mouthguards and skin patches, were utilized to measure head impact kinematics, with peak linear acceleration consistently reported across all studies. Results reveal significant heterogeneity in peak linear and rotational acceleration, highlighting the complexity of quantifying impact magnitudes in rugby. Impact location analysis indicated side impacts as most prevalent (44%), followed by frontal (29%) and back impacts (19%). Notably, concussive events yielded a pooled peak linear acceleration estimate of 63.01 g, with the RL cohort exhibiting higher acceleration than RU. Conclusion: This study contributes to the growing body of literature on head impacts in rugby; identifying available evidence on the magnitude and location of head impacts measured by sensors, and emphasizing the importance of wearable sensor technology in advancing player safety and informing injury management practices. Despite the valuable insights provided, limitations, including methodological inconsistencies and study heterogeneity, underscore the need for cautious interpretation. Further research is warranted to standardize protocols and enhance the understanding of effective injury prevention strategies in rugby. PROSPERO registration number: CRD42023480779 (20 November 2023).